Kepuasan Kerja: Lingkungan Kerja, Role Stress, dan Kompensasi Finansial - Viandita Wahyu Sukmakirana; Nurwanti Nurwanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to determine the effect of Work Environment, Role Stress and Financial Compensation on Job Satisfaction. The population in this study were employees of Operation Directorate at PT X. Samples were obtained using a saturated sampling technique and data were collected by distributing questionnaires. Respondents involved in this study amounted to 67 employees. Data were analyzed using Simple Regression and Multiple Linear Regression. Based on the hypothesis test, the results of this study are Work Environment, Role Stress and Financial Compensation have a significant effect on Job Satisfaction.